Highly Ordered Amorphous Silicon-Carbon Alloys Obtained by RF PECVD - I. Pereyra (Brazilian Journal of Physics, 2000)
We have shown that close to stoichiometry RF PECVD amorphous silicon carbon alloys deposited under silane starving plasma conditions exhibit a tendency towards c-SiC chemical order. Motivated by this trend, we further explore the effect of increasing RF power and H2 dilution of the gaseous mixtures, aiming to obtain the amorphous counterpart of c-SiC by the RF-PECVD technique. Doping experiments were also performed on ordered material using phosphorus and nitrogen as donor impurities and boron and aluminum as acceptor ones. For nitrogen a doping efficiency close to device quality a-Si:H was obtained, the lower activation energy being 0,12 eV with room temperature dark conductivity of 2.10-3 (omega.cm). Nitrogen doping efficiency was higher than phosphorous for all studied samples. For p-type doping, results indicate that, even though the attained conductivity values are not device levels, aluminum doping conducted to a promising shift in the Fermi level. Also, aluminum resulted a more efficient acceptor than boron, in accordance to observations in crystalline SiC material.